Utilizing Video to Support Planning, Enacting, and Analyzing Teaching in Preservice Science Teacher Education - Barnhart, Tara (Innovations in Science Teacher Education, 2022)
The use of video to support preservice teacher development is becoming increasingly common. However, research on teacher noticing indicates that novices need tools to focus their attention on students’ disciplinary ideas. This article describes a course designed for secondary science teachers that incorporates video analysis as a core part of repeated learning cycles. Of particular interest is how well the video-analysis tasks and tools support PSTs in learning to plan, enact, analyze, and reflect on instruction. A qualitative analysis of PSTs’ video annotations, lesson-analysis guides, and written reflections reveals that PSTs in the course developed a disposition towards responsive instruction and leveraged evidence of student thinking in their analyses of the effectiveness of their instruction. Lesson-analysis guides appear to be the tool PSTs relied on the most to inform their written reflections. Further investigation on how best to structure video analysis will help further refine the use of video in teacher education.